Service Quality and Internationalisation – A Case Study of Malaysian Telecommunication Company - Mohd Fadzil, Norazlinda (2005)
In today’s globalised and borderless market, delivering high service quality is a crucial for the growth of any organisation. Customer has been the focus of any successful business and the success depends on organisations understanding and meeting customers’ needs and demands. Thus, the development of service quality is imperative for businesses to progress through understanding and meeting needs and demands, which also a contributing factor to profitability,sustaining competitive advantage (Hampton, 1993; Zeithaml and Bitner., 2000)and making their presence internationally (Boston and Sims, 2000; Lander, 2000;Oyama, 2000). However, delivering high service quality and its potential for positioning service firms internationally has yet to be fully explored (Clark and Rajaratnam, 1999).